2005
DOI: 10.1007/s00421-005-1357-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exercise-induced muscle damage on maximal intensity intermittent exercise performance

Abstract: Exercise-induced muscle damage (EIMD) is a common occurrence following activities with a high eccentric component. Alterations to the torque-velocity relationship following EIMD would appear to have serious implications for athletic performance, particularly as they relate to impairment of maximal intensity exercise. However, this has been studied infrequently. The purpose of this study was to assess the effects of EIMD on maximal intermittent sprint performance. Ten male participants (age 22.4 +/- 3.2 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
141
1
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(166 citation statements)
references
References 44 publications
15
141
1
9
Order By: Relevance
“…It is well established that physical performance is detrimentally effected by EIMD, with a number of studies showing reductions in peak power generation, jump performance and time trial exercise (Byrne and Eston, 2002;Twist and Eston, 2005;Burt and Twist, 2011). Consistent with our hypothesis as indicated in Figure 1a, and when observing a large effect size (η 2 p 0.39), high dose EPA supplementation attenuated the decrement in average squat jump performance (-2.1%) in comparison to both low dose EPA (-9.8%) and placebo (-8.3%) supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that physical performance is detrimentally effected by EIMD, with a number of studies showing reductions in peak power generation, jump performance and time trial exercise (Byrne and Eston, 2002;Twist and Eston, 2005;Burt and Twist, 2011). Consistent with our hypothesis as indicated in Figure 1a, and when observing a large effect size (η 2 p 0.39), high dose EPA supplementation attenuated the decrement in average squat jump performance (-2.1%) in comparison to both low dose EPA (-9.8%) and placebo (-8.3%) supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were instructed to assume an un-weighted squat of approximately 90° and mark their perceived soreness on a horizontal line between 0 and 10 ( Twist and Eston, 2005).…”
Section: Perceived Muscle Sorenessmentioning
confidence: 99%
“…Studies have reported that strength training impaired running economy (RE) 8 hours post (Palmer and Sleivert, 2001) and compromised running time-trial performance (Marcora and Bosio, 2007) and repeated sprint ability (Twist and Eston, 2005) 24 hours post. In contrast, studies have shown no eŠect on RE 24 hours following strength training despite increases in creatine kinase and muscle soreness (Marcora and Bosio, 2007;Paschalis et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, theseˆndings suggest that strength training may impair sub-maximal endurance performance on the same day yet cause no aŠect the following day, or aŠect maximal endurance performance the following day. However, these studies (Marcora and Bosio, 2007;Paschalis, et al, 2007;Twist and Eston, 2005) collected endurance performance measures following a single training session. To date, the eŠect of combining the two modes of exercises on the same day and their eŠect on various performance measures the following day remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…DOMS pain and loss of strength arises from damage to muscle fibers, muscle fatigue due to lactic acid and creatine kinase accumulation, degradation of connective tissue and fascia structure, muscle spasms, decrease of afferent inputs and inflammation (2,(5)(6)(7)(17)(18)(19)(20)(21). DOMS and strength loss reach their maximum value within 24-48 hours following eccentric fatigue protocol or eccentric training (2,(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%